Alterations in the Antimicrobial Resistance Profile of Acinetobacter baumannii Strains Isolated from Intensive Care Unit Patients: Five-Year Follow-up in Cappadocia - Nazife Akman; PELİN ÖZMEN; Mustafa Türk (Microbes, Infection and Chemotherapy)
Background: This study aims to determine alterations in the antibiotic resistance status of Acinetobacter baumannii strains isolated from lower respiratory tract samples of patients in intensive care units over the years. Methods: In this comprehensive study, A. baumannii strains isolated from aspirate and sputum samples of patients hospitalized in intensive care units of a second-stage state hospital between January 2018 and December 2022 were meticulously and retrospectively investigated and analyzed for antimicrobial resistance. Results: The rate of aspirate and sputum samples in the study was 18.1% (754/4151); The positivity rate of cultures was 51.7% (390/754); The rate of those associated with A. baumannii was found to be 65.6% (256/390).. 90.2% of the isolates were isolated from the general intensive care unit (231/256). The rates of A. baumannii isolated from aspirate and sputum samples were 67.4% (213/316) and 58.1% (43/74), respectively. The carbapenem resistance rate in A. baumannii isolates grown in aspirate samples was 96.5%, fluoroquinolone resistance was 91.7%; The carbapenem resistance rate in sputum samples was 96.1% and fluoroquinolone resistance was 90.9%. The most effective antibiotics against A. baumannii strains isolated from both aspirate and sputum samples were colistin 100% (n=256), TMP/SXT 55.8% (143/256), tigecycline 50.3% (129/256), respectively. Conclusion: Our study reveals a concerning trend-a high frequency of multidrug-resistant A. baumannii isolates are being identified in the Central Anatolia region of our country. This high prevalence, which is a cause for immediate concern, underscores the urgent and immediate need for robust infection control measures to curb the spread of A. baumannii in hospitals.